Peduli dan Membangun : Studi Pendampingan Teologis terhadap Pelecehan Seksual dalam Komunitas Gerejawi - Debora Atika Pasya Montjai; Rheinhard Rheinhard; Lisa Elisabet; Yusmi Diana Sampe; Yuni Tangke Datu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Sexual harassment is a criminal act carried out by two people by force with the intention of satisfying lust or an act of revenge. Sexual harassment in the church community is an act that violates Christian teachings where it is carried out outside the basis of marriage. Sexual harassment is carried out by force between men and women outside the husband and wife couple, namely between parents and children or between father and child. The Church has an important role in this. The Church seeks to heal, support, treat, and even accompany victims of sexual abuse through pastoral actions. Sexuality is no longer something taboo to talk about, therefore it is important for the church, government, and even families to discuss sexuality from an early age as an effort to prevent criminal acts or sexual violence. Society must have a sense of empathy and sympathy for victims of sexual violence, as an effort to heal and accept the reality experienced by victims. The church must really act in a real way in spiritual and psychological and social healing of victims.